2021
DOI: 10.22271/phyto.2021.v10.i2q.13990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage condition on physiochemical and sensory properties of papaya jam

Abstract: The objective of present study was to evaluate the effect of storage condition on physiochemical and sensory properties of jam prepared from ripe and unripe papaya. Jam was prepared by traditional Open Kettle method. Jams were stored at ambient condition and low temperature for 60 days. Results exhibited that moisture, TSS, pH, total sugar and phenolics content of jam gradual changed during storage. There was decrease in the moisture, pH and phenolics content during storage period. However, TSS and total sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…On the other hand, the aroma of the product made with mango purée at a TSS of 60°Bx and dried to a moisture content of 10% was described as better compared to the product blended to a TSS of 67°Bx. A previous report revealed that a TSS of 63°Bx was suitable for the production of papaya jam bars [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the aroma of the product made with mango purée at a TSS of 60°Bx and dried to a moisture content of 10% was described as better compared to the product blended to a TSS of 67°Bx. A previous report revealed that a TSS of 63°Bx was suitable for the production of papaya jam bars [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides undergo acid hydrolysis during storage, so soluble sugars are released in the food product, causing an increase in total soluble solids [ 43 ]. In ripe and unripe Papaya, a significant increase in Total Soluble Solids (TSS) was observed for 60 days [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Menurut Nafri et al, (2021) konsentrasi gula total akan sangat rendah saat pertumbuhan pertama pada buah, kemudian berbeda pada saat buah mengalami pematangan yang berakibat pada peningkatan gula total dengan wujud glukosa dan juga fruktosa. Peningkatan kadar gula bisa menjadi salah satu ciri pematangan pada buah.…”
Section: Kadar Gula Totalunclassified